Strategy and Evaluation of The Implementation of Moral Values at Islamic Universities - Rohita Rohita; Rizqi Maulida (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2020)
Penerapan nilai-nilai Islam pada Perguruan Tinggi Islam merupakan hal yang diterapkan dalam tiap aspek kehidupan kampus dan oleh seluruh civitas academia kampus. Nilai-nilai Islam adalah hasil eloborasi antara aturan yang berlaku dengan aspek ibadah dan moralitas. Penerapannya berhubungan dengan perilaku tiap individu hubungannya dengan Allah dan dengan manusia. Penelitian ini bertujuan untuk penerapan nilai-nilai Islam di Perguruan Tinggi Islam. Metode yang digunakan dalam penelitian ini ialah kualitatif dengan wawancara mendalam, observasi dan studi dokumen. Penelitian ini dilakukan pada tiga Perguruan Tinggi Islam yaitu UIN Syarif Hidayatullah Jakarta, Universitas Al Azhar Indonesia dan Universitas Muhammadiyyah Jakarta dengan nara sumber berasal dari pimpinan kampus, fakultas, staf dan mahasiswa. Hasil penelitian ini menunjukkan bahwa penerapan nilai-nilai Islam pada tiga Perguruan Tinggi tersebut sudah terlaksana namun belum optimal. Hal yang menjadi kendala ialah hambatan pada penerapan ini baik level atas hingga bawah ditambah lagi kebijakan yang belum tertulis atau tersedia pada buku pedoman penerapan. Belum adanya Standar dalam evaluasi penerapan nilai Islam menjadi kendala dalam penerapan sehingga tidak dapat diketahui kategori atau tingkatan penerapan nilai-nilai Islam.(The implementation of Islamic values in campus life is the realization of Islamic values in the form of norms in every aspect of campus life carried out by all levels of the campus community. The elaboration of Islamic values is embodied in the form of legal norms, state, and morals framed in aspects of worship and morality. However, the realization is associated with the behavior of each individual in relation to Allah (hablumminallah) and its relationship with humans (hablumminanas). The purpose of this study is to know the depiction of the application of Islamic values in Islamic universities.The method used is qualitative research method with in-depth interview, documentation, and observation. This research was conducted at three Islamic universities, namely UIN Syarif Hidayatullah Jakarta, UAI, and UMJ with sources from university leaders, faculties, departments, staffs and students. The results show that Islamic values have been applied at the three campuses but not yet optimal, because there are obstacles both at the level of leaders and at the level of students and staff. Barriers at the level of leaders related to the policy agreement to apply Islamic values for all academic communities that affects the availability of a guidebook containing Islamic values. The guidebook could not be used effectively as a medium of socialization for all academic communities. These obstacles also affect the evaluation of the implementation of Islamic values, where the three campuses do not have a standard for evaluation to use in all parts of campuses. Therefore, it is difficult to know the level of the application of Islamic values.)